The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1121/1.5023687
|View full text |Cite
|
Sign up to set email alerts
|

Auditory enhancement under simultaneous masking in normal-hearing and hearing-impaired listeners

Abstract: Auditory enhancement, where a target sound within a masker is rendered more audible by the prior presentation of the masker alone, may play an important role in auditory perception under variable everyday acoustic conditions. Cochlear hearing loss may reduce enhancement effects, potentially contributing to the difficulties experienced by hearing-impaired (HI) individuals in noisy and reverberant environments. However, it remains unknown whether, and by how much, enhancement under simultaneous masking is reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Similar to the paradigm used in this study, various psychophysical and neural phenomena have shown the influence of preceding signals on the following target tone perception, termed as “auditory enhancement” (e.g. Nelson and Young, 2010; Kreft et al, 2018). In these studies, the preceding maskers were broadband noise with a spectral notch around the target signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the paradigm used in this study, various psychophysical and neural phenomena have shown the influence of preceding signals on the following target tone perception, termed as “auditory enhancement” (e.g. Nelson and Young, 2010; Kreft et al, 2018). In these studies, the preceding maskers were broadband noise with a spectral notch around the target signal.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism of “auditory enhancement” has been attributed to the adaptation at both low- and high-level auditory processing. For supporting the adaptation at low-level auditory processing, Kreft et al (2018) suggested that olivocochlear efferents may induce the adaptation effect in a longer time scale than the auditory nerve fibers (Guinan Jr, 2006). If this is the case, how modulation patterns (e.g., RR, RC, CC , and FC ) result in different degrees of CMR reduction is in question.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting finding is that enhancement is observed under simultaneous masking, but not under forward masking for both cochlear-implant users [18] and hearing-impaired listeners [19,20]. This intriguing difference suggests a potential difference in mechanism underlying enhancement in simultaneous vs. forward masking, which has yet to be fully elucidated.…”
Section: Effects Of Hearing Loss and Cochlear Implants Onmentioning
confidence: 97%
“…Auditory Enhancement Two recent studies in our lab have explored auditory enhancement in both cochlear-implant users [18] and listeners with sensorineural hearing loss of presumed cochlear origin [19]. In both cases, detection thresholds for a pure tone in the presence of spectrally flanking masker tones were reduced by the introduction of a precursor that was a copy of the masker.…”
Section: Effects Of Hearing Loss and Cochlear Implants Onmentioning
confidence: 99%
“…The enhancement effect is distinct from the effect measured in the current study. The enhancement effect (e.g., [58]) refers to the increased audibility of a given target signal component of a spectral complex by prior exposure to the spectral complex with the target signal component deleted; this is suggested to be due to an increase in gain in the (neutrally) unadapted frequency region (adaptation inhibition). The latter example refers to enhancement in the case of a single unmasked target tone.…”
Section: Precursor Effect In the Light Of Various Proposed Underlying Processesmentioning
confidence: 99%